Effects of split direct-injected hydrogen strategies on combustion and emissions performance of a small-scale rotary engine. (15th January 2021) - Shi, Cheng; Ji, Changwei; Ge, Yunshan; Wang, Shuofeng; Yang, Jinxin; Wang, Huaiyu
Abstract: To achieve more efficient and robust combustion, split direct-injected hydrogen as a new injection strategy for rotary engines was used to clarify the influences of various injection parameters, including hydrogen amount for each pulse, the dwell between pulses, and secondary injection pulse-width, on combustion performance and emissions formation by CFD modeling. The results of this investigation confirmed the benefit of split direct-injection as a useful means to govern mixture stratification which enabled the combustion more effective and rapid compared to single-injection mode. Enhanced combustion could be achieved by increasing the mass fraction of post-injection with an optimized dwell between injections. Further investigation on secondary injection pulse-width demonstrated that engine performance was substantially improved with a wider second injection pulse. From one side, as the secondary injection pulse-width was increased, the surrounding mixture distribution of the spark-plug location was richer, which was confirmed as a beneficial inhomogeneous circumstance of hydrogen to accelerate the burning rate. From another side, strong tumble level and turbulence intensity were of significant importance for facilitating the combustion process and getting optimal thermal efficiency. For emissions formation, split direct-injected hydrogen made a near-zero HC and CO emissions at the price of a comparable increase of NOx emissions. Highlights: Hydrogen split direct-injection is implemented on a gasoline SI Wankel engine. Analyzing three factors for amelioration including first, post-injection, and dwell. Split injection strategies can realize desirable stratified conditions of hydrogen. Injecting proper hydrogen in each pulse with an adequate dwell is of importance. Thermal efficiency can be notably improved benefits from the wide second injection.